Electrolyte interference resistant solid carbonate electrode, preparation method and use method
By forming a nano-lead coating and a lead carbonate sensitive film on the lead wire, and covering the solid carbonate electrode of the nano-microporous polyvinyl chloride film, combined with Ag/Ag2Se or Ag/Ag2S electrodes, the accuracy of carbon dioxide concentration measurement in high-voltage seawater is solved. The problem is to achieve accurate online detection of carbon dioxide concentration and water environment monitoring.
Patent Information
- Application Number
- CN202411308120.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art is difficult to accurately detect the actual concentration of carbon dioxide in deep seawater in high pressure states online, especially in the sampling process under high pressure states, gas dissolved components are prone to volatilization losses, resulting in inaccurate analysis results.
Using a solid carbonate electrode that resists electrolyte interference, a nano-lead coating and a lead carbonate sensitive film are formed on the lead wire, and a nano-microporous polyvinyl chloride film is covered as an electrode with all solid structure, combining Ag/Ag2Se or Ag/ The Ag2S electrode was used as the reference electrode and the potential difference was measured to calculate the carbon dioxide concentration.
Accurate online detection of the concentration of dissolved carbon dioxide in the aqueous medium, avoiding interference from water-soluble electrolytes on the electrode, the electrode structure is strong and has strong anti-interference ability, and is suitable for real-time monitoring of various aqueous mediums.
Smart Images

Figure CN119290997A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrode preparation, and in particular relates to a solid carbonate electrode resistant to electrolyte interference, and a preparation and use method thereof. Background Art
[0002] Carbon dioxide dissolved in seawater is the largest carbon reservoir on Earth. The exchange of carbon dioxide between seawater and the atmosphere has an important impact on the global climate and the human living environment. The increase in the concentration of dissolved carbon dioxide in seawater will lead to ocean acidification and deteriorate the marine ecological environment. The concentration of carbon dioxide in water bodies can be used as an indicator of biological and microbial metabolic activities. It is also an important component of natural fluids such as volcanoes, mud volcanoes, submarine hydrothermal fluids, and submarine hydrocarbon seeps. The total dissolved CO2 content in water media is an important environmental assessment parameter. It is of great significance for understanding the activities of aquatic organisms and microorganisms, as well as the carbon cycle between the hydrosphere and the atmosphere. The total dissolved CO2 content is also one of the important parameters for understanding industrial fermentation and many chemical processes.
[0003] Since carbon dioxide gas is volatile, conventional sampling and analysis cannot accurately reflect the actual concentration of carbon dioxide in water. Especially in deep seawater under high pressure, the gas dissolved components will inevitably volatilize and be lost due to the pressure drop during sampling. Therefore, it is urgent to provide a solid carbonate electrode that is resistant to electrolyte interference for online detection of dissolved carbon dioxide concentration in water media. Summary of the invention
[0004] The purpose of the present invention is to solve the deficiencies of the prior art, to meet the needs of online detection of dissolved carbon dioxide concentration in marine environment, microbial metabolism and industrial processes, and to provide a solid carbonate electrode resistant to electrolyte interference, as well as a preparation and use method.
[0005] The specific technical solutions adopted by the present invention are as follows:
[0006] In a first aspect, the present invention provides a solid carbonate electrode resistant to electrolyte interference, which comprises, from the inside to the outside, a lead wire used as a substrate and a conductor, a nano-lead coating, a lead carbonate sensitive membrane, and a nano-microporous polyvinyl chloride membrane.
[0007] In a second aspect, the present invention provides a method for preparing a solid carbonate electrode resistant to electrolyte interference, the specific steps are as follows:
[0008] S1: using an AC power supply, connecting the lead wire to be plated to the negative electrode of the power supply, connecting the positive electrode of the power supply to the positive electrode of the diode, and connecting the negative electrode of the diode to the anode lead wire; placing the lead wire to be plated in a plating solution, electroplating the lead wire on the negative electrode of the power supply to generate a nano lead plating layer;
[0009] S2: Using an electrochemical method, a lead wire with a nano-lead coating on its surface is used as a working electrode, and is scanned in a bicarbonate solution to generate a lead carbonate sensitive membrane, thereby obtaining a carbonate ion selective electrode embryo;
[0010] S3: Dipping the carbonate ion selective electrode embryo obtained in step S2 into a film-forming agent and then taking it out, standing it upright with the detection end facing upward, so that a nanoporous polyvinyl chloride film is formed on the surface of the carbonate ion selective electrode embryo; the solute in the film-forming agent is polyvinyl chloride, and the solvent is a mixture of tetrahydrofuran and cyclohexanone;
[0011] S4: placing the carbonate ion selective electrode embryo with nanoporous polyvinyl chloride membrane obtained in step S3 in an extract to remove residual film-forming agent; and obtaining a solid carbonate electrode resistant to electrolyte interference after drying.
[0012] Preferably, the electroplating solution is prepared by dissolving lead nitrate in ethylene glycol or dimethyl sulfoxide solvent, and the concentration of lead nitrate in the electroplating solution is 3% to 10%.
[0013] Preferably, the AC power supply in step S1 adopts a function signal generator, and the working parameters of the electroplating are set as follows: sine wave, voltage 1.0-1.3V, frequency 50-100Hz, and electroplating time 50-100 seconds.
[0014] Preferably, in the electrochemical method described in step S2, a platinum electrode is used as the counter electrode, and an Ag / Ag2Se or Ag / Ag2S electrode is used as the reference electrode; the electrochemical method described in step S2 is set as follows: linear voltammetry, scanning voltage range -1.2 to -0.5 V, sensitivity 10 -3 A, scan 5 to 10 times, scanning speed 0.1 to 0.01 V / s.
[0015] Preferably, the bicarbonate in step S2 is ammonium bicarbonate or sodium bicarbonate.
[0016] Preferably, the mass ratio of tetrahydrofuran to cyclohexanone in the film-forming agent in step S3 is 1:(2-3); and the mass concentration of polyvinyl chloride in the film-forming agent is 5%-10%.
[0017] Preferably, in step S3, the carbonate ion selective electrode embryo is dipped in the film-forming agent and then placed vertically for 10 to 30 minutes; the extractant in step S4 is methanol or ethanol, and the carbonate ion selective electrode embryo after the reaction is placed in methanol or ethanol for washing for 5 to 15 minutes.
[0018] In a third aspect, the present invention provides a solid carbonate electrode resistant to electrolyte interference prepared by the preparation method of the solid carbonate electrode described in the second aspect.
[0019] In a fourth aspect, the present invention provides a method for using a solid carbonate electrode that is resistant to electrolyte interference, wherein the solid carbonate electrode described in the first aspect or the third aspect is used as a working electrode, and an Ag / Ag2Se or Ag / Ag2S electrode is used as a reference electrode; the working electrode and the reference electrode are both placed in a water body to be tested containing carbonate ions, and the potential difference between the working electrode and the reference electrode is measured; and the concentration of carbonate ions in the solution to be tested is obtained by conversion using a calibration formula.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The solid carbonate electrode with resistance to electrolyte interference provided by the present invention is a fully solid structure and does not contain an internal reference electrolyte solution. The electrode is compact and has a solid structure. The outermost nanoporous PVC membrane can shield the interference of water-soluble electrolytes on the ion-selective membrane.
[0022] (2) In terms of usage, Ag / Ag2Se or Ag / Ag2S electrode is used as the reference electrode to avoid interference of chloride ions and other anions in the water body to the reference electrode, thereby improving the anti-interference ability of the detection electrode pair. The carbonate electrode provided by the present invention and the matching reference electrode are suitable for detecting the dissolved carbonate content in various water media, based on which the concentration of dissolved carbon dioxide in water can be calculated. In addition to carbonate, the electrode is also sensitive to Pb in water. 2+ It has the same Nernst response and can also be used to detect the content of dissolved lead ions in water. It has a wide range of uses in water environment monitoring, real-time online detection in the field of chemistry and chemical engineering, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope image of the lead wire to be plated initially in Example 1, with a magnification of 30,000 times;
[0024] Figure 2 This is a scanning electron microscope image of the lead wire with a nano-lead coating formed on the surface in Example 1, with a magnification of 30,000 times;
[0025] Figure 3 This is a scanning electron microscope image of a carbonate ion selective electrode embryo with a lead carbonate sensitive membrane in Example 1, with a magnification of 30,000 times;
[0026] Figure 4 The EDS spectrum analysis result of the surface of the solid carbonate ion electrode prepared in Example 1;
[0027] Figure 5 The calibration results in carbonate ion solutions of different concentrations in Example 3;
[0028] Figure 6 This is the calibration curve in Example 3. DETAILED DESCRIPTION
[0029] The present invention is further described and illustrated below in conjunction with the accompanying drawings and specific embodiments. The technical features of each embodiment of the present invention can be combined accordingly without conflicting with each other.
[0030] The invention provides a solid carbonate electrode resistant to electrolyte interference, which comprises, from inside to outside, a lead wire used as a substrate and a conductor, a nano-lead plating layer, a lead carbonate sensitive membrane and a nano-microporous polyvinyl chloride membrane.
[0031] Lead wire is selected as the electrode substrate and conductor because it has high electrochemical activity. The nano-lead coating formed by electroplating can penetrate into the lead wire, significantly reducing the interface impedance between the composite film and the substrate lead wire. The nano-lead coating on the lead wire forms a complete coating on the lead wire. Nano-lead has good conductivity. It plays the role of a conductive layer between the metal substrate and the outer carbonate sensitive membrane, replacing the role of the electrolyte solution in the liquid membrane electrode. Lead carbonate is the core component of the carbonate sensitive membrane. The two are a microscopic composite, and each nano-lead particle is coated with lead carbonate. Lead carbonate is a sparingly soluble salt and exists in a dissolution-precipitation equilibrium with carbonate in the water medium. The carbonate ion concentration in the water body to be measured will cause a change in the surface potential of the lead / lead carbonate membrane material, forming a concentration response to the measured object; the relationship between the lead carbonate membrane and the nano-lead particles is an in-situ composite relationship, and the response signal on the sensitive membrane can be transmitted to the substrate lead wire through the nano-lead coating and detected by the sensor. The nano-microporous polyvinyl chloride (PVC) membrane located on the outermost layer of the electrode plays a shielding and protective role. Due to the presence of a large amount of dissolved salt in seawater, high concentrations of anions and cations will interfere with the selectivity of carbonate-sensitive membranes for carbonate ions in seawater. The nanoporous polyvinyl chloride (PVC) membrane coated on the surface of the electrode is hydrophobic and can block hydrophilic anions and cations outside the electrode without affecting the performance of the electrode, while carbonate ions can selectively pass through. In addition, the nanoporous polyvinyl chloride (PVC) membrane can also slow down chemical corrosion and extend the service life of the electrode.
[0032] The present invention also provides a method for preparing a solid carbonate electrode resistant to electrolyte interference, the specific steps of which are as follows:
[0033] (1) Using an AC power supply, connect the lead wire to be plated to the negative pole of the power supply, connect the positive pole of the power supply to the positive pole of the diode, and connect the negative pole of the diode to the anode lead wire; place the lead wire to be plated in a plating solution, and electroplate the lead wire on the negative pole of the power supply to generate a nano-lead plating layer. The working parameters of the electroplating are set as: sine wave, voltage 1.0-1.3V, frequency 50-100Hz, and electroplating time 50-100 seconds.
[0034] The AC power supply can be a function signal generator. The power supply of the function signal generator is an AC with a sine wave waveform, and the positive electric field portion is retained after diode rectification. During the electroplating process, the lead ions in the electroplating solution move toward the lead wire to be plated under the action of the electric field, and are reduced to elemental lead after obtaining electrons. The negative lead wire is dissolved during the electroplating process to replenish the cations lost in the electroplating solution. The alternating current emitted by the function signal generator inhibits the growth of lead particles during the electroplating process, and the electroplating results in the formation of a nano-lead film on the lead wire to be plated. The film penetrates into the surface of the substrate lead wire, and there is no obvious interface impedance between the conductive layer and the substrate.
[0035] (2) Using an electrochemical method, a lead wire with a nano-lead coating on its surface is used as a working electrode and scanned in a bicarbonate solution to generate a lead carbonate sensitive membrane and obtain a carbonate ion selective electrode embryo. The working parameters of the electrochemical method are: linear voltammetry, scanning voltage range, sensitivity 10 -3 A, scan 5 to 10 times, scanning speed 0.1 to 0.01 V / s.
[0036] According to the standard electrode potential table, the reaction: Pb + CO3 2- =PbCO3+2e - The potential value relative to the standard hydrogen electrode is -0.506 V. In the voltage range of -1.2 to -0.5 V, as the electrochemical workstation scans, the elemental lead reacts with the carbonate in the reaction solution to form a lead carbonate sensitive film on the surface of the nano-lead particles.
[0037] (3) Dipping the carbonate ion selective electrode embryo obtained in step (2) into the film-forming agent and taking it out, standing it upright with the detection end facing upward, so that a nanoporous polyvinyl chloride film is formed on the surface of the carbonate ion selective electrode embryo.
[0038] The solute in the film-forming agent is polyvinyl chloride, and the solvent is a mixture of tetrahydrofuran (THF) and cyclohexanone (CHA). The mass ratio of tetrahydrofuran to cyclohexanone is 1:(2-3); the mass concentration of polyvinyl chloride in the film-forming agent is 5%-10%. The boiling points of the two solvents CHA and THF are significantly different, wherein the boiling point of THF is 66°C and the boiling point of CHA is 155°C. The former can volatilize quickly at room temperature; the latter has a small loss due to natural volatilization at room temperature.
[0039] After the carbonate ion selective electrode coated with carbonate sensitive membrane is dipped into the film former solution, the electrode should be immediately inverted, that is, the detection end is facing upward, so that the film former solution can flow and spread naturally to avoid the solution from accumulating at the end of the electrode. After standing and drying in the air for 10 to 30 minutes, the solvent THF is basically volatilized and the PVC is basically solidified, but the other solvent CHA remains in the PVC and is evenly dispersed in the initial film in the form of emulsion droplets.
[0040] (4) placing the carbonate ion selective electrode embryo with nanoporous polyvinyl chloride membrane obtained in step (3) in an extract to remove residual film-forming agent; and obtaining a solid carbonate electrode resistant to electrolyte interference after drying.
[0041] The residual CHA will be dissolved and leave nano-sized permeable micropores on the initial membrane. The hydrophobic PVC membrane with nano-pores can shield hydrophilic interfering components, while the dissolved carbonate can selectively penetrate, thereby improving the anti-interference ability of the electrode.
[0042] The present invention also provides a method for using a solid carbonate electrode that is resistant to electrolyte interference, wherein the solid carbonate electrode described in the first aspect or the third aspect is used as a working electrode, and an Ag / Ag2Se or Ag / Ag2S electrode is used as a reference electrode; the working electrode and the reference electrode are both placed in a water body to be tested containing carbonate ions, and the potential difference between the working electrode and the reference electrode is measured; and the concentration of carbonate ions in the solution to be tested is obtained by conversion using a calibration formula.
[0043] Usually, the ion selective electrode uses Ag / AgCl electrode as the reference electrode, but in the environment with high ionic strength, such as seawater, salt lake and other high salinity environments, the dissolved Cl in the water - Ions will form a response on the Ag / AgCl electrode, interfering with the potential signal between the reference electrode and the working electrode. In addition, carbonate, sulfate, phosphate, which are common in natural water bodies, and hydrogen sulfide in reducing water bodies, can all combine with silver, and the solubility product of the formed chemical is higher than that of silver chloride, so they can interfere with the Ag / AgCl electrode and corrode the sensitive membrane of the electrode. The solubility product of Ag2Se is 63.7, and the solubility product of Ag2S is 50.1, which are much higher than other silver salt compounds. Therefore, when using Ag / Ag2Se or Ag / Ag2S electrodes as reference electrodes, the possibility of interference from other anions is theoretically very small. This is the theoretical basis for the electrode pairs with Ag / Ag2Se and Ag / Ag2S electrodes as reference electrodes to have higher resistance to electrolyte interference.
[0044] Said Ag / Ag2Se or Ag / Ag2S can be prepared as follows:
[0045] (1) Electroplating nanosilver on silver wire. Use a function signal generator as a power source, connect the silver wire to be plated to the negative pole of the function signal generator, connect the positive pole to the positive pole of the diode, connect the negative pole of the diode to the anode silver wire, and place the silver wire to be plated and the anode silver wire in a silver nitrate solution with a concentration of 0.01 to 0.1 M. The working parameters are set as follows: sine wave, voltage 0.5 to 1.0 V, frequency 50 to 100 Hz, and electroplating time 50 to 100 seconds.
[0046] Using alternating current as the power source can inhibit the growth of metal particles during the electroplating process, which is conducive to the formation of single-substance nano-scale particles on the surface of the metal substrate. The coating composed of nanoparticles is not only the carrier of the sensitive film, but also the conductive layer between the sensitive film and the substrate. There is no obvious interface impedance between the nanosilver and the silver wire of the substrate, which effectively reduces the internal resistance of the electrode and is conducive to improving the detection sensitivity.
[0047] (2) Generating Ag2Se or Ag2S film on the surface of nanosilver. The part electroplated with nanosilver is immersed in a sodium sulfide or ammonium sulfide solution with a concentration of 0.05 to 0.1 M for 30 to 60 minutes, and an Ag2S film is formed on the surface of the nanosilver to obtain an Ag / Ag2S electrode; the part electroplated with nanosilver is immersed in a sodium selenide solution with a concentration of 0.01 to 0.1 M for 60 to 120 minutes, and an Ag2Se film is formed on the surface of the nanosilver to obtain an Ag / Ag2Se electrode.
[0048] Nanosilver has a high specific surface area and surface electrochemical activity. When silver wires plated with nanosilver are immersed in sodium sulfide or ammonium sulfide solutions, silver selenide or silver sulfide films will quickly form on their surfaces. Since the solubility product of silver selenide and silver sulfide is much higher than that of other silver salt compounds, using Ag / Ag2Se or Ag / Ag2S electrodes as reference electrodes can significantly improve the ability of electrodes to resist electrolyte interference.
[0049] Example 1
[0050] This embodiment provides a method for preparing a solid carbonate electrode resistant to electrolyte interference, and the specific steps are as follows:
[0051] (1) Cut a silver wire with a length of 40 mm and a diameter of 0.5 mm, and polish the surface of the silver wire with sandpaper with a polishing degree of 1000 mesh and 5000 mesh respectively. After polishing, ultrasonic cleaning is carried out in 0.1M nitric acid solution, acetone and ultrapure water for 10 minutes to remove the oxide layer and oil stains on the metal surface. After cleaning, the surface moisture is absorbed with dust-free paper. A function signal generator is used as a power supply. The silver wire to be plated is connected to the negative pole of the function signal generator, the positive pole is connected to the positive pole of the diode, and the negative pole of the diode is connected to the anode silver wire. The silver wire to be plated and the anode silver wire are placed in a silver nitrate solution with a concentration of 0.01M. The working parameters are set as: sine wave, voltage 1V, frequency 50Hz, and electroplating time 60 seconds. A silver wire with nanosilver plated on the surface is obtained. The part plated with nanosilver was immersed in a 0.1M sodium sulfide solution (pH=10) for 30 minutes to form an Ag2S film on the surface of the nanosilver. The Ag / Ag2S reference electrode was obtained by washing with deionized water and drying.
[0052] (2) Cut a lead wire with a length of 40 mm and a diameter of 0.5 mm, and ultrasonically clean it in acetone and ultrapure water for 10 minutes respectively. Then, soak the lead wire in 1M nitric acid for 10 seconds, clean it, and dry the surface moisture with dust-free paper to prepare the lead wire to be plated. Dissolve 1g of lead nitrate in 9g of dimethyl sulfoxide solution to obtain a plating solution with a concentration of 10%.
[0053] (3) Using a function signal generator as a power source, connect the lead wire to be plated to the negative pole of the power source, connect the positive pole of the power source to the positive pole of the diode, and connect the negative pole of the diode to the anode lead wire; place the lead wire to be plated in the electroplating solution, electroplate the lead wire on the negative pole of the power source to generate a nano-lead coating. The working parameters are set as: sine wave, voltage 1.2V, frequency 50Hz, electroplating time 100 seconds.
[0054] (4) Using an electrochemical workstation, in a 0.1 M ammonium bicarbonate solution, a lead wire with a nano-lead coating on its surface was used as the working electrode, a platinum electrode was used as the counter electrode, and an Ag / Ag2S electrode was used as the reference electrode. Linear voltammetry was used with a scanning voltage range of -1.2 to -0.5 V and a sensitivity of 10 -3 A, scan 5 times, the scanning speed is 0.01V / s, generate lead carbonate sensitive membrane, and obtain carbonate ion selective electrode embryo.
[0055] (5) Cyclohexanone and tetrahydrofuran are mixed in a mass ratio of 1:3 to obtain a mixed solvent; 0.5 g of polyvinyl chloride (PVC) is dissolved in 9.5 g of the mixed solvent, and magnetic stirring is performed until it is completely dissolved to obtain a film-forming agent with a concentration of 5%. The carbonate ion selective electrode embryo obtained in step (4) is dipped in the film-forming agent and then taken out, and the probe end is facing upward, and the embryo is placed upright at room temperature for 10 minutes to form a nanoporous polyvinyl chloride film on the surface of the carbonate ion selective electrode embryo.
[0056] (6) placing the carbonate ion selective electrode embryo with nanoporous polyvinyl chloride membrane obtained in step (5) in methanol for 5 minutes to remove the residual film-forming agent, and drying it to obtain a solid carbonate electrode resistant to electrolyte interference.
[0057] The solid carbonate electrode resistant to electrolyte interference prepared in Example 1 was subjected to scanning electron microscopy and energy spectrum analysis:
[0058] Figure 1 This is a scanning electron microscope image of the lead wire after being soaked in nitric acid, with a magnification of 30,000 times. It can be seen that the rough surface of the lead wire formed by corrosion increases the subsequent adhesion to the lead carbonate sensitive film. Figure 2 This is a scanning electron microscope image of nano-lead formed by electroplating on the surface of the lead wire. The magnification is 30,000 times. It can be observed that the rough surface of the lead wire has been covered by nano-lead. Figure 3This is a scanning electron microscope image of the lead carbonate sensitive film of the solid-state carbonate ion electrode, with a magnification of 30,000 times. It can be observed that the surface of the nano-lead has been completely transformed into nanosheets with a size of 100 to 200 nm. The interlaced sheets also have small nano-scale holes, which bring a larger specific surface area. Figure 4 This is the EDS energy spectrum analysis result of the surface of the solid carbonate ion electrode resistant to electrolyte interference, showing Pb, C and O, indicating that the chemical composition of the sensitive membrane material is PbCO3, and the structure of the carbonate ion selective electrode is lead wire-nanolead-lead carbonate sensitive membrane.
[0059] Example 2
[0060] This embodiment provides a method for preparing a solid carbonate electrode resistant to electrolyte interference, and the specific steps are as follows:
[0061] (1) Cut a 40mm long silver wire with a diameter of 0.5mm, and polish the surface of the silver wire with sandpaper with a polishing degree of 1000 mesh and 5000 mesh respectively. After polishing, ultrasonic cleaning is carried out in 0.1M nitric acid solution, acetone and ultrapure water for 10 minutes to remove the oxide layer and oil stains on the metal surface. After cleaning, the surface moisture is absorbed with dust-free paper. Use a function signal generator as a power supply, connect the silver wire to the negative pole of the function signal generator, connect the positive pole to the positive pole of the diode, and connect the negative pole of the diode to the anode silver wire. The silver wire to be plated and the anode silver wire are placed in a silver nitrate solution with a concentration of 0.01M. The working parameters are set as: sine wave, voltage 0.8V, frequency 50Hz, electroplating time 100 seconds. A silver wire with nanosilver plated on the surface is obtained. The part plated with nanosilver was immersed in a 0.1M sodium selenide solution (pH=10) for 45 minutes to form an Ag2Se film on the surface of the nanosilver. The Ag / Ag2Se reference electrode was obtained by washing with deionized water and drying.
[0062] (2) Cut a lead wire with a length of 40 mm and a diameter of 0.5 mm, and ultrasonically clean it in acetone and ultrapure water for 10 minutes respectively. Then, soak the lead wire in 1M nitric acid for 10 seconds, clean it, and dry the surface moisture with dust-free paper to prepare the lead wire to be plated. Dissolve 0.5 g of lead nitrate in 9.5 g of ethylene glycol solution to obtain a plating solution with a concentration of 5%.
[0063] (3) Using a function signal generator as a power source, connect the lead wire to be plated to the negative pole of the power source, connect the positive pole of the power source to the positive pole of the diode, and connect the negative pole of the diode to the anode lead wire; place the lead wire to be plated in the electroplating solution, electroplate the lead wire on the negative pole of the power source to generate a nano-lead coating. The working parameters are set as: sine wave, voltage 1V, frequency 100Hz, and electroplating time 80 seconds.
[0064] (4) Using an electrochemical workstation, in a 0.1 M sodium bicarbonate solution, a lead wire with a nano-lead coating on its surface was used as the working electrode, a platinum electrode was used as the counter electrode, and an Ag / Ag2Se electrode was used as the reference electrode. Linear voltammetry was used with a scanning voltage range of -0.8 to -0.5 V and a sensitivity of 10 -3 A, scan 10 times, the scanning speed is 0.1V / s, generate lead carbonate sensitive membrane, and obtain carbonate ion selective electrode embryo.
[0065] (5) Cyclohexanone and tetrahydrofuran are mixed in a mass ratio of 1:2 to obtain a mixed solvent; 1 g of polyvinyl chloride (PVC) is dissolved in 9 g of the mixed solvent, and magnetic stirring is performed until it is completely dissolved to obtain a film-forming agent with a concentration of 10%. The carbonate ion selective electrode embryo obtained in step (4) is dipped in the film-forming agent and then taken out, and the probe end is facing upward, and the embryo is placed upright at room temperature for 10 minutes to form a nanoporous polyvinyl chloride film on the surface of the carbonate ion selective electrode embryo.
[0066] (6) placing the carbonate ion selective electrode embryo with nanoporous polyvinyl chloride membrane obtained in step (5) in methanol for 5 minutes to remove the residual film-forming agent, and drying it to obtain a solid carbonate electrode resistant to electrolyte interference.
[0067] Example 3
[0068] This embodiment provides a method for using the carbonate ion electrode resistant to electrolyte interference prepared in Embodiment 1, which is specifically as follows:
[0069] Carbonic acid is a weak acid that will ionize in water. The ionization process can be divided into two steps, corresponding to the mutual conversion of carbonic acid, bicarbonate and carbonate, with ionization constants K1 and K2 respectively. When pH>8.3, the dissolved carbon dioxide in the water is completely converted into carbonate and bicarbonate. In the test conditions of this embodiment, the pH of the solution is greater than 8.3, so there is no need to consider the effect of dissolved carbon dioxide on the carbonate concentration. At this time, the carbonate content can be calculated according to formula (1):
[0070]
[0071] Where: C is the total inorganic carbon in the solution, K1 = 10 -6.35 , K2=10 -10.33 .
[0072] (1) Prepare standard solutions with different carbonate ion concentrations. The standard solutions with different carbonate ion concentrations used in this embodiment are prepared by mixing sodium bicarbonate and sodium carbonate solutions of the same concentration to adjust the pH. The mother liquor is 1L simulated seawater containing 24.72g sodium chloride, 0.67g potassium chloride, 1.36g calcium chloride, 4.66g magnesium chloride, and 6.29g magnesium sulfate, and 0.1M and 0.01M sodium carbonate and sodium bicarbonate seawater solutions are prepared. Mix in different proportions, record the pH value of the solution, and then calculate it by formula (1). Details are shown in Table 1.
[0073] Table 1 Standard solutions with different carbonate ion concentrations
[0074] Total inorganic carbon / M pH Carbonate concentration / M 0.1 8.4 <![CDATA[10 -2.94 ]]> 0.1 8.75 <![CDATA[10 -2.6 ]]> 0.1 9.0 <![CDATA[10 -2.3 ]]> 0.1 9.35 <![CDATA[10 -2.02 ]]> 0.1 9.7 <![CDATA[10 -1.72 ]]> 0.01 8.5 <![CDATA[10 -3.84 ]]> 0.01 9.0 <![CDATA[10 -3.35 ]]>
[0075] (2) Using a solid carbonate ion electrode as the working electrode and an Ag / Ag2S electrode as the reference electrode, the above standard solutions were tested respectively. The test time of each standard solution was 200 s, and the potential difference between the working electrode and the reference electrode was measured.
[0076] like Figure 5 As shown in the figure, it can be seen that the carbonate ion selective electrode -2.02 M, 10 -2.3 M, 10 -2.6 M, 10 -2.94 M, 10 -3.35 M, 10 -3.84 The response time in the carbonate ion solution of M is about 50s, and it has good stability. At this time, the pH value of the solution is 8.4-9.35. At pH 9.7, the response of the electrode is abnormal, the potential gradient is abnormal, and a stable potential cannot be obtained. This is because as the pH increases, the OH in the solution - It reacted with the lead carbonate sensitive film on the electrode surface, indicating that the suitable environmental pH value of this carbonate ion selective electrode needs to be less than 9.35.
[0077] like Figure 6 As shown, the solid carbonate ion electrode is 2- The Nernst linear response in the solution is good, and the potential difference is linearly related to the carbonate ion concentration in the standard solution, and the calibration formula is E = -28.779lg (CO3 2- )-640.95, the electrode slope is -28.779mV / dec (the ideal Nernst slope value of divalent cation is 29.59mV / dec), R 2 =0.9996.
[0078] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A solid carbonate electrode resistant to electrolyte interference, characterized in that: From the inside to the outside, there are lead wire used as substrate and conductor, nano-lead coating, lead carbonate sensitive membrane and nano-porous polyvinyl chloride membrane.
2. A method for preparing a solid carbonate electrode resistant to electrolyte interference, characterized in that: The specific steps are as follows: S1: using an AC power supply, connecting the lead wire to be plated to the negative electrode of the power supply, connecting the positive electrode of the power supply to the positive electrode of the diode, and connecting the negative electrode of the diode to the anode lead wire; placing the lead wire to be plated in a plating solution, electroplating the lead wire on the negative electrode of the power supply to generate a nano lead plating layer; S2: Using an electrochemical method, a lead wire with a nano-lead coating on its surface is used as a working electrode, and is scanned in a bicarbonate solution to generate a lead carbonate sensitive membrane, thereby obtaining a carbonate ion selective electrode embryo; S3: Dipping the carbonate ion selective electrode embryo obtained in step S2 into a film-forming agent and then taking it out, standing it upright with the detection end facing upward, so that a nanoporous polyvinyl chloride film is formed on the surface of the carbonate ion selective electrode embryo; the solute in the film-forming agent is polyvinyl chloride, and the solvent is a mixture of tetrahydrofuran and cyclohexanone; S4: placing the carbonate ion selective electrode embryo with nanoporous polyvinyl chloride membrane obtained in step S3 in an extract to remove residual film-forming agent; and obtaining a solid carbonate electrode resistant to electrolyte interference after drying.
3. The method for preparing a solid carbonate electrode resistant to electrolyte interference according to claim 2, characterized in that: The electroplating solution is prepared by dissolving lead nitrate in ethylene glycol or dimethyl sulfoxide solvent, and the concentration of the lead nitrate in the electroplating solution is 3% to 10%.
4. The method for preparing a solid carbonate electrode resistant to electrolyte interference according to claim 2, characterized in that: The AC power source in step S1 uses a function signal generator, and the working parameters of the electroplating are set as follows: sine wave, voltage 1.0-1.3V, frequency 50-100Hz, and electroplating time 50-100 seconds.
5. The method for preparing a solid carbonate electrode resistant to electrolyte interference according to claim 2, characterized in that: In the electrochemical method described in step S2, a platinum electrode is used as the counter electrode, and an Ag / Ag2Se or Ag / Ag2S electrode is used as the reference electrode; the electrochemical method described in step S2 is set as follows: linear voltammetry, scanning voltage range -1.2 to -0.5 V, sensitivity 10 -3 A, scan 5 to 10 times, scanning speed 0.1 to 0.01 V / s.
6. The method for preparing a solid carbonate electrode resistant to electrolyte interference according to claim 2, characterized in that: The bicarbonate in step S2 is ammonium bicarbonate or sodium bicarbonate.
7. The method for preparing a solid carbonate electrode resistant to electrolyte interference according to claim 2, characterized in that: The mass ratio of tetrahydrofuran to cyclohexanone in the film-forming agent in step S3 is 1:(2-3); the mass concentration of polyvinyl chloride in the film-forming agent is 5%-10%.
8. The method for preparing a solid carbonate electrode resistant to electrolyte interference according to claim 2, characterized in that: In step S3, the carbonate ion selective electrode embryo is dipped in the film-forming agent and then placed vertically for 10 to 30 minutes; in step S4, the extractant is methanol or ethanol, and the carbonate ion selective electrode embryo after the reaction is placed in methanol or ethanol for washing for 5 to 15 minutes.
9. A solid carbonate electrode resistant to electrolyte interference prepared by the method for preparing a solid carbonate electrode according to any one of claims 2 to 8.
10. A method for using a solid carbonate electrode resistant to electrolyte interference, characterized in that: The solid carbonate electrode according to claim 1 or 9 is used as a working electrode, and the Ag / Ag2Se or Ag / Ag2S electrode is used as a reference electrode; the working electrode and the reference electrode are both placed in a water body to be detected containing carbonate ions, and the potential difference between the working electrode and the reference electrode is measured; The concentration of carbonate ions in the solution to be tested is obtained by conversion using the calibration formula.